Social Media Impact of Articles Published by Dermatology Residents During Medical School: Cross-sectional Study - Austin Huang; Harrison Zhu; Kelvin Zhou; R Parker Kirby; Nina Dasari; Gianmarco A Calderara; Kathryn Cordova; Ryan Sorensen; Anshul Bhatnagar; Soo Jung Kim (JMIR Publications, 2022)
BackgroundThe Altmetric score (AS) is a novel measure of publication impact that is calculated by the number of mentions across various social media websites. This method may have advantages over traditional bibliometrics in the context of research by medical students. ObjectiveThis study aimed to determine whether dermatology matriculants who graduated from higher-ranked medical schools published more articles with greater impact (ie, a higher AS) than those from lower-ranked institutions. MethodsA PubMed search for articles published by dermatology residents who started medical school in 2020 was conducted. Demographic information and Altmetric data were collected, and medical schools were sorted according to US News' top-25 and non-top-25 categories. ResultsResidents who completed their medical training at a top-25 institution published more papers (mean 4.93, SD 4.18 vs mean 3.11, SD 3.32; P<.001) and accrued a significantly higher total AS (mean 67.9, SD 160 vs mean 22.9, SD 75.9; P<.001) and average AS (mean 13.1, SD 23.7 vs mean 6.71, SD 32.3; P<.001) per article than those who graduated from non-top-25 schools. ConclusionsOur results indicate that students in top-25 schools may have greater access to research resources and opportunities. With a pass/fail United States Medical Licensing Examination Step 1 exam that may increasingly shift focus toward scholarly output from medical students, further discussion on how to create a more equitable dermatology match is essential.